Bangkitnya Eksistensi: Digital Marketing sebagai Peningkatan Daya Tarik Terhadap Potensi Wisata Air Terjun Siwalangan di Desa Kindingan Kabupaten Hulu Sungai Tengah - Dewi, Tiara Kusuma; Hidayah, Sri; Hanifah; Salma, Ratu; Ardanata, Stevany Nike; Nasuha, Habibi Adam; Noorsyifa, Gusti; Noorfallah, Ananda; Sauki, Ahmad; Syahla, Mayang Effiena; Hermawan, Rio (Prodi Sosiologi FISIP ULM, 2024)
This community service program aimed to develop tourism strategies that could enhance the attractiveness of the Siwalangan Waterfall tourist spot in Kindingan Village, Hulu Sungai Tengah Regency. Various activities were conducted, including aligning perceptions, researching tourism development strategies, training in digital marketing, creating local craft outlets, hosting a tourism festival, and producing a short film to promote the village's tourism potential. The digital marketing training was designed to introduce modern promotional techniques to the community, to increase tourist appeal. Additionally, the establishment of local craft outlets aimed to support the village's creative economy. The results of this program indicated an increase in the community’s knowledge about digital marketing and awareness of the importance of sustainable tourism management. Moreover, the availability of supporting facilities and promotion through digital marketing successfully broadened the exposure of Siwalangan Waterfall's tourism potential, which is expected to attract more visitors. However, challenges encountered during the program ismplementation included a lack of awareness among some community members about the sustainability of tourism. To address this, further programs focused on education and enhancing community participation in tourism management are necessary to optimally and sustainably maximize the village's tourism potential. This program lasted for 58 days, utilizing a live-in participatory approach, whereby the team resided in the village throughout the service and were actively engaging in community activities beyond the program itself.